Wound Healing Potential of Paspalum scrobiculatum Linn. in Streptozotocin-induced Diabetic Rats: Wound Healing Potential of Paspalum scrobiculatum Linn. in Streptozotocin-induced Diabetic Rats - Saini, Pooja (International Journal of Pharmaceutical & Biological Archive, 2019)
Aim of the Study: The aim is to study the evaluation of the wound healing properties of ethyl acetate and ethanolic extracts of roots of Paspalum scrobiculatum in diabetic rats. Materials and Methods: Ethyl acetate and ethanolic extracts (100, 200, and 400 mg/Kg body weight) were administered orally to male Wistar albino rats. Streptozotocin was used to induce irreversible diabetes mellitus and excision wound healing method for determining wound healing activity for 21 days. Results: Ethyl acetate and ethanolic extracts at different dose levels produced the decrease in fasting blood glucose in a dose-dependent manner. After 14 days, the maximum reduction in fasting blood glucose (211.00 mg/dl and 224.50 mg/dl) was observed in diabetic rats treated with ethanolic extract at 400 and 200 mg/kg dose, respectively. A momentary decrease in blood glucose level was also observed in the ethyl acetate extract-treated rats at a dose of 400 mg/kg. The maximum percentage contraction in wound area (27.60–98.51% and 24.13–93.96%) was observed in diabetic rats treated with ethanolic extract at 400 and 200 mg/kg dose, respectively, on the 15th day of 21 days’ study. Conclusion: The study reveals that P. scrobiculatum has wound healing activity along with antidiabetic activity, thereby mitigating its conventional uses and amplify it into an allopathic system of medicine.